Changes in erythrocyte deformability in patients with T2DM are associated with RBC energy metabolism - SUN Ming-yue, LI Xu-yan, SA Ru-la, LI Jing-jing, LIANG Hao, YAN Zhao-li, SU Yan (Jichu yixue yu linchuang, 2021)
Objective To investigate the relationship between erythrocyte (RBC) deformability and RBC energy metabolism in patients with type 2 diabetes mellitus (T2DM). Methods Totally 80 T2DM and 50 controls with age of 40 to 70 years were selected. Rough hematology laboratory test, ATP content, Hexokinase (HK) and Pyruvate kinase (PK) activity were detected.Results BMI, DBP and SBP of patients with T2DM were higher than those of control group (P＜0.05). T2DM of RBC deformation index (TK), rigidity index(IR), RBC distribution width (RDW) and average RBC volume (MCV) were higher than that of control group (P＜0.05); The content of ATP and PK activity in RBC of T2DM group were higher than that of control group (P＜0.05), while the activity of HK was lower than that of control group(P＜0.05). In the T2DM, TK was negatively correlated with ATP content and HK activity, and positively correlated with HbA1c. IR was negatively correlated with HK and PK values, and positively correlated with HbA1c (P＜0.05). Compared with Group A, the TK value of Group C increased (P＜0.05) in the HbA1c group. Compared with Group A, Group C had higher ATP, PK and HK (P＜0.05). Compared with Group A, ROS in Group C increased (P＜0.05). Results RCD damage in diabetic patients is closely related to HbA1c, and RBC energy metabolism plays an important role in maintaining RCD. In diabetic patients, ATP production in RBC increased, PK activity increased, and energy metabolism was vigorous, but this did not improve the reduced RCD status caused by high glucose. Conclusions The energy metabolism of erythrocytes in diabetic patients was more vigorous and is closely related to the decrease of RCD. RCD reduction is a risk factor for diabetic microangiopathy, so monitoring erythrocytes energy metabolism may provide a new basis for monitoring the progress of clinical diabetes patients and support clinical diagnosis and treatment.